SPEAKING â€“ WRITING MODE: STRATEGIES IN TRANSFORMING SPOKEN AND WRITTEN LANGUAGE - Maldin, Siska Amelia (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2013)
There is a tendency of cases in transforming spoken and written language. A current debate was proposed about the role. This debate derives from current phenomenon which shows evidence which is related with learner mastery in the particular skills. Some learners are able to produce spoken form of language fluently, however, when it comes to writing, it is seen that they find difficulties and get disturbance to put down ideas and elaborate the ideas into a good writing. Â Hence, two questions arise. First, to what extent is the nature of spoken and written language? Second, what are strategies to help learners in transforming their spoken language to the written production? Therefore, this article is proposed to explain the nature of spoken and written language and present any strategies to help learners in transforming their spoken language into the written forms.